Pemetaan Sebaran Tempat Pembuangan Sampah Sementara (TPS) Secara Spasial di Kecamatan Alam Barajo Kota Jambi - Maliki Maliki; G. M Saragih; Siti Umi Kalsum (Jurnal Daur Lingkungan, 2022)
Alam Barajo Subdistrict is a division of Kota Baru Subdistrict, Jambi City with the area covering Kenali Besar Village, Rawasari Village, Mayang Mangurai Village, Bagan Pete Village and Beliung Village. There are many TPS in this area, either on the side of the road, near rivers, bushes, or in locations in the form of concrete boxes and containers provided by the government. A tool to analyze the number of TPS in question using GIS with ArcMap 10.8 software. The problem taken is the number of distribution points of TPS locations. Based on the results of the analysis found 33 TPS locations. Rawasari Village found 7 TPS locations, Kenali Besar Village found 12 TPS locations, Beliung Village found 3 TPS locations, Bagan Pete Village found 4 TPS locations, and Mayang Mangurai Village found 7 TPS locations.